Consolidating Molecular Logic with New Solid‐Bound YES and PASS 1 Gates and Their Combinations. Issue 13 (25th April 2017) - McKinney, Bernadine O. F.; Daly, Brian; Yao, Chaoyi; Schroeder, Marc; de Silva, A. Prasanna
Abstract: Proton‐driven YES and PASS 1 molecular logic tags based on anthracene and 4‐aminonaphthalimide fluorophores, emitting blue and green, respectively, are employed on amino‐terminated polyethylene glycol–polystyrene and aminopropyl silica particles. The (YES+PASS 1) logic combination is also a distinguishable tag in both colours. The scope of such tags is delineated. Abstract : Bound by logic : Fluorescent photoinduced electron transfer switches are put to work as logic tags for molecular computational identification of polymeric objects (see figure). The logic tags are based on anthracene and 4‐aminonaphthalimide fluorophores, emitting blue and green, respectively, and are employed on amino‐terminated polyethylene glycol–polystyrene and aminopropyl silica particles.